Defenses in contemporary international criminal law - Knoops, Geert-Jan G. J. (International and comparative criminal law series)
Methodology for determining a uniform system of international criminal law defenses -- International criminal law defenses originating from customary international law -- International criminal law defenses originating from comparative criminal law -- The diverging position of criminal law defenses before the ICTY and ICC : contemporary developments -- Individual and institutional command responsibility and the international regulation of armed conflicts -- International criminal law defenses and the international regulation of armed conflicts -- Self-defense by states and individuals in the law of war -- Contemporary and new technical issues of international criminal law defenses -- A new concept of international due process